Impact of Gercus Formation Erosion and Rock Sliding on Duhok Dam Reservoir – Northern Iraq - Al-Talib, Sahad Ali; Al-Jawadi, Azealdeen Salih; Al-Sanjari, Abdul Sattar A. (Iraqi Journal of Science, 2021)
The environmental impact was illustrated by rockslide and erosion on the Duhok Dam and its reservoir. The evaluation of the geotechnical characteristics of the Gercus Formation was conducted. The research plan was divided into three phases, field, laboratory, and office works. The fieldwork included studying all the geological phenomena of the region related to the environmental impact. The laboratory work focused on studying the geotechnical properties of the various rock samples taken from the Gercus Formation. Rocklab program was used to define the geotechnical properties of a rock mass. The results indicated the weak resistance of the Gercus Formation rocks to weathering and erosion processes, as well as their weak resistance to sliding. These results indicate a kind of risk for this formation on the stability of the dam, as well as its effect on the size of the reservoir storage, due to erosion and deposition of huge amounts of sediments in the dam reservoir.